2012
DOI: 10.1083/jcb.201110058
|View full text |Cite
|
Sign up to set email alerts
|

DRP1-dependent mitochondrial fission initiates follicle cell differentiation during Drosophila oogenesis

Abstract: Reduced Drp1-mediated mitochondrial fission decreases cell cycle exit and prevents Notch-dependent follicle cell differentiation during oogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
83
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(98 citation statements)
references
References 28 publications
13
83
2
Order By: Relevance
“…After stage 6, the follicle cells exit the mitotic cycle to terminally differentiate into the epithelial cell layer, which is further patterned into various cell types (Klusza and Deng, 2011). We have previously reported differential mitochondrial regulation in the mitotic follicle cells and the differentiated-patterned main body follicle cells (MBCs) and posterior follicle cells (PFCs) (Mitra et al, 2012). Here, we found that the mtDmCycE pool was significantly higher in the MBCs than the PFCs or the mitotic follicle cells ( Fig.…”
Section: Detection Of a New Mitochondria-associated Pool Of Cyce In Msupporting
confidence: 56%
See 3 more Smart Citations
“…After stage 6, the follicle cells exit the mitotic cycle to terminally differentiate into the epithelial cell layer, which is further patterned into various cell types (Klusza and Deng, 2011). We have previously reported differential mitochondrial regulation in the mitotic follicle cells and the differentiated-patterned main body follicle cells (MBCs) and posterior follicle cells (PFCs) (Mitra et al, 2012). Here, we found that the mtDmCycE pool was significantly higher in the MBCs than the PFCs or the mitotic follicle cells ( Fig.…”
Section: Detection Of a New Mitochondria-associated Pool Of Cyce In Msupporting
confidence: 56%
“…We next sought to detect the new mtCycE pool in vivo in the Drosophila follicle cell layer where we have previously demonstrated specific mitochondrial regulation of CycE (Mitra et al, 2012). The follicle cell layer is the epithelial cell layer encapsulating the Drosophila egg chambers.…”
Section: Detection Of a New Mitochondria-associated Pool Of Cyce In Mmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to its well-recognized role as the 'powerhouse' of the cell, recent studies have indicated that the mitochondria control many more cellular functions (Mitra and Lippincott-Schwartz, 2010;Antico Arciuch et al, 2012;Friedman and Nunnari, 2014). For example, the mitochondrial network in the cell appears to be electrically coupled (De Giorgi et al, 2000) and coordinates such critical processes as cell death, cell proliferation, autophagy (Rambold and Lippincott-Schwartz, 2011), cell differentiation (Mitra et al, 2012) and aging (Lee and Wei, 2012). The view seems to be emerging that perhaps the mitochondrial network is actually the 'brains' of the cell, controlling much of the cell's processes, including activities of the nucleus.…”
Section: Partnering With Microbesmentioning
confidence: 99%